The Mediating Effect of Frailty in the Relationship between Depression and Falls among Older People Living Alone in Korea - Yeon-Ha Kim; Jung Min Cho (Tehran University of Medical Sciences, 2022)
Background: We explored the potential mediating role of frailty in the relationship between depression and falls. Methods: The participants were 1,408 community-dwelling older people living alone in South Korea. The potential mediating role of frailty in the relationship between depression and falls was evaluated through univariate and multivariate logistic regression. Baron and Kenny's three-step criteria for mediation were used to examine the mediating effect. Results: Frailty fully mediated the association between severe depression and falls in univariate (t=11.58, P<.05) and multivariate (t=10.42, P<.05) analyses. Conclusion: Frailty is a valuable target for fall interventions in severely depressed older people living alone.